2021
DOI: 10.1101/2021.02.08.430188
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maternal obesity programs white and brown adipose tissue transcriptome and lipidome in offspring in a sex-dependent manner

Abstract: The prevalence of overweight and obesity among children has drastically increased during the last decades and maternal obesity has been demonstrated as one of the ultimate factors. Nutrition-stimulated transgenerational epigenetic regulation of key metabolic genes is fundamental to the developmental origins of the metabolic syndrome. Fetal nutrition may differently influence female and male offspring. In this work, we investigated the sex-dependent programming of maternal obesity in visceral, subcutaneous and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…We previously demonstrated that MO leads to a sexually dimorphic reprogramming of hepatic lipid composition and gene expression, and that this also occurs when the offspring receive a postweaning control diet. We also showed that other organs are affected in a sex-dependent manner 15 . We now show that MO offspring fed an obesogenic diet have sex-specifically altered liver lipidomes explained by accompanying changes in the transcriptomes.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…We previously demonstrated that MO leads to a sexually dimorphic reprogramming of hepatic lipid composition and gene expression, and that this also occurs when the offspring receive a postweaning control diet. We also showed that other organs are affected in a sex-dependent manner 15 . We now show that MO offspring fed an obesogenic diet have sex-specifically altered liver lipidomes explained by accompanying changes in the transcriptomes.…”
Section: Discussionsupporting
confidence: 58%
“…Most importantly, we confirm our previous findings that MO modulates hepatic TG molecular species in female but not in male offspring 14 . Somewhat surprising, we demonstrated that MO regulates the gene expression in white adipose in male offspring towards an inflammatory pattern, while instead altering it towards more browning and oxidative phosphorylation patterns in females 15 . The mechanisms by which MO can differently modulate epigenetic marks in utero between sexes and between tissues remain intriguing and require further investigation.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations